Development of an immersive sound tool for RPG sessions using Pure Data and MobMuPlat - Rocha, Gabriel L.; Oliveira, João P. M.; Schiavoni, Flávio L. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
Role-playing games (RPGs) are an important niche within the gaming market. They aim to entertain players by immersing them in a fictional universe. To achieve this, narrative resources are used, and in some cases, different supporting tools are employed. Among these tools, the use of audio, such as soundscapes and soundtracks, can be considered. This article presents the development of software that allows an RPG game master to control various sounds to create environments for their players. This tool is developed using the Pure Data programming language and the MobMuPlat platform.